2007
DOI: 10.1590/s0004-282x2007000100011
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated to the positive cerebrospinal fuid culture in the tuberculous meningitis

Abstract: -Central nervous system involvement is the most common neurological complication in the course of tuberculosis. The lack of rapid and sensitive tests delays the early diagnosis. Here, we retrospectively reviewed the cerebrospinal fluid (CSF) examination of 30 patients with tuberculous meningitis confirmed by bacteriological tests (culture and/or polymerase chain reaction). The purpose of the present study was to determine the CSF parameters associated to the positive CSF culture for Mycobacterium tuberculosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 16 publications
(38 reference statements)
2
25
0
4
Order By: Relevance
“…Several studies have reported an increase in the prevalence of CNS-TB under conditions of immune suppression, e.g., in HIV-coinfected patients, who often present with low CD4 ϩ T cell counts (49,50). M. tuberculosis bacilli are more likely to be detected in the cerebrospinal fluid (CSF) of immunosuppressed patients (51,52), possibly due to higher levels of bacilli and of dissemination. As a key requirement to control M. tuberculosis bacillus replication (53), low CD4 ϩ T cell counts could predispose such patients to increased levels of CNS bacilli.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an increase in the prevalence of CNS-TB under conditions of immune suppression, e.g., in HIV-coinfected patients, who often present with low CD4 ϩ T cell counts (49,50). M. tuberculosis bacilli are more likely to be detected in the cerebrospinal fluid (CSF) of immunosuppressed patients (51,52), possibly due to higher levels of bacilli and of dissemination. As a key requirement to control M. tuberculosis bacillus replication (53), low CD4 ϩ T cell counts could predispose such patients to increased levels of CNS bacilli.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, harsh culture conditions and time-consuming culture operations are major bottlenecks for the early diagnosis of TBM. Although several rapid culture systems such as BACTEC and ESP have been established in recent years, their extensive use in developing countries and underdeveloped regions still remains difficult (11)(12)(13). Therefore, clinical features and routine laboratory examinations remain the chief methods for the differential diagnosis of TBM and BM (14).…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis (TB) remains among the leading infectious causes of death in developing nations, with Mycobacterium tuberculosis (M. tuberculosis; MT) as the species responsible for most of these deaths (1,2). According to the World Health Organization (WHO), in 2014, the estimated number of tuberculosis cases was 9 million, including 3.5 million new cases and 1.1 million human immunodeficiency virus (HIV)-positive cases.…”
Section: Introductionmentioning
confidence: 99%